Back Cover Image, Volume 94, Number 6, June 2022. Issue 6 (15th April 2022) - Hernandez, Matthew M.; Riollano‐Cruz, Mariawy; Boyle, Mary C.; Banu, Radhika; Shrestha, Paras; Gray, Brandon; Cao, Liyong; Chen, Feng; Shi, Huanzhi; Paniz‐Perez, Daniel E.; Paniz‐Perez, Paul A.; Rishi, Aryan L.; et al.
Abstract : Back Cover Caption : The cover image is based on the Research Article Food for thought: Eating before saliva collection and interference with SARS‐CoV‐2 detection by Matthew M. Hernandez et al., https://doi.org/10.1002/jmv.27660 .